Caesarean Section for Non-Medical Reasons: A Rising Public Health Issue - Dhakal Rai, Sulochana; Teijlingen, Edwin van; Regmi, Pramod R.; Wood, Juliet; Dangal, Ganesh; Dhakal, Keshar Bahadur (Journal of Karnali Academy of Health Sciences, 2021)
Background: Caesarean section (CS) is a life-saving surgical intervention for childbirth. Emphasis is given to performing CS only for valid medical reasons. However, performing CS on non-medical indications is increasing worldwide. The scoping review aims to explore the non-medical reasons for performing CS.Methods: Articles on CS for non-medical reasons were searched using several electronic databases: PubMed, MEDLINE, CINAHL and open access journal databases such as Nepal journals online (NepJOL) and Bangladesh journals online (BanglaJOL). Additional articles were searched from the reference list of the selected articles and organizational websites. Eligible full-text articles were appraised, and relevant data were extracted. A narrative synthesis of extracted data was performed using content analysis.Results: Maternal request is the most common non-medical indication of performing CS. The main reason for women’s preference for a CS is to avoid labour pain followed by certainty/convenience, avoid damage to the pelvic floor and vaginal trauma, and safer for baby. Similarly, the main reason for requesting a CS is fear of labour pain followed by fear of childbirth, safer mode of birth for both mother and baby and maintaining pelvic floor integrity. The main reasons of willingness to perform CS by obstetrician were fear of litigation, financial incentives and convenience. The ethical aspect of non-medically indicated CS remains complex.Conclusions: Performing CS without medical indications is a rising public health issue which has created medical, financial and ethical dilemmas in obstetrics care. The reasons for maternal request for a CS should be explored well. Obstetric care must include education of pregnant women on mode of childbirth including indications, risks and benefits of CS during antenatal visits.